Desain UI/UX Website Menggunakan Metode Lean UX - Purwaningtias, Fitri; Ulfa, Maria (Journal of Information Technology Ampera, 2024)
Nyemiliciouss adalah usaha yang bergerak di bidang makanan sejak tahun 2022. Selama ini Nyemiliciouss melakukan proses bisnis produk hanya melalui Instagram dan juga dari mulut ke mulut. Dengan penjualan seperti ini dirasakan belum optimal untuk bisa menawarkan produk yang dijual ataupun memasarkan produk secara luas. Nyemiliciouss juga belum memiliki website sehingga sebelum pembuatan website diperlukan desain UI/UX website untuk mengetahui apakah website yang akan dibuat telah sesuai dengan yang diharapkan. Desain UI/UX dibuat dengan menggunakan Figma. Desain UI/UX ini dibuat menggunakan metode Lean UX dengan 4 tahapan yaitu, declare assumptions, create an mvp, run an experiment dan feedback and research. Selanjutnya dilakukan evaluasi menggunakan User Experience Questionnaire (UEQ) dimana ada 6 indikator yang mengahsilkan indikator daya tarik nilai rata-rata 1,90 kategori “Excellent”, indikator kejelasan nilai rata-rata 1,88 kategori “Good”, indikator efisiensi nilai 1,85 kategori “Good”, indikator ketepatan nilai 1,92 kategori “Excellent”, stimulasi nilai rata-rata 1,70 kategori “Good” dan keterbaruan dengan nilai 1,80 “Excellent”. Nyemiliciouss is a business that has been operating in the food sector since 2022. So far, Nyemiliciouss has carried out the product business process only through Instagram and also through word of mouth. With sales like this, it is felt that it is not optimal to be able to offer products for sale or market products widely. Nyemiliciouss doesn’t have a website, so before creating a website, a website UI/UX design created using Figma. This UI/UX design was created using the Lean UX method with 4 stages, namely, declare assumptions, create an mvp, run an experiment and feedback and research. Next, an evaluation was carried out using the User Experience Questionnaire (UEQ) where there were 6 indicators which produced an attractiveness indicator with an average value of 1.90 in the “Excellent” category, a clarity indicator with an average value of 1.88 in the “Good” category, an efficiency indicator with a value 1.85 in the “Good” category, accuracy indicator value 1.92 in the “Excellent” category, stimulation average value of 1.70 in the “Good” category and recency with a value of 1.80 “Excellent”.